Effectiveness of a Moodle based Life Skills Education (LSE) Module for Prospective Teachers - Kaur, Jagpreet (JOURNAL OF INDIAN EDUCATION, 2023)
Moodle is a learning management system which is designed to enable the educators to create effective online courses using its free and open source software. In the present study, Moodle was used as a platform to develop an online Life Skills Education (LSE) course. Life skills education focuses on the overall personality development of the child by enabling them to handle any kind of life situation. It also encourages them to face their struggles to achieve their targets. The main aim of the present study is to develop a moodle based life skills education module for prospective teachers and investigate its effectiveness on attitude and awareness of teachers regarding life skills education. The study was conducted following a quasi experimental research design on a cluster sample of 100 prospective teachers. The sample of the study was taken from the intact classes of M.Ed. first and second year students from Department of Education, Punjabi University, Patiala using cluster sampling technique (N=100). Attitude towards life skills education scale and life skills awareness test along with an online course on life skills education using Moodle platform based on the 10 life skills as identified by World Health Organisation were prepared by the investigator to conduct the present study. The data was analysed with the help of analysis of covariance technique. The results revealed that moodle based life skills education module has a significant and positive effect on attitude and awareness of prospective teachers regarding life skills education as compared to traditional method of teaching. Implications of these results are discussed in the context of teacher education. *